Content domain, measurement, and validity of the red tape concept: a second-order confirmatory factor analysis - Coursey, David H.; Pandey, Sanjay K. (2007)
Red tape, generally defined as burdensome rules and procedures, is a relatively new construct unique to the public management literature. Like many public management constructs, red tape has received scant measurement attention. This study uses second-order confirmatory factor analysis to test two varying theoretical perspectives, one that treats red tape as a formative index, derived from inflexibility in various management subsystems (e.g., budgeting, personnel), and the other as a reflective scale where political accountability and other external influences drive red tape. Results for 16 items designated across five subdimensions suggest better support for the reflective scale perspective. Implications for red tape research are discussed. - Reproduced.
Keywords: Public administration